Excitation and Propagation of Longitudinal L (0, 2) Mode Ultrasonic Guided Waves for the Detection of Damages in Hexagonal Pipes: Numerical and Experimental Studies. (23rd April 2021) - Wan, Xiang; Liu, Meiru; Zhang, Xuhui; Fan, Hongwei; Mao, Qinghua; Dong, Ming; Wang, Xing; Ma, Hongwei
Abstract : The hexagonal pipe is a special kind of tube structure. Its inner surface of the cross section is in the shape of circle, while the outer surface is hexagonal. It has functioned as an essential and critical part of a drill stem in a high-torque drill machine used in various resource exploitation fields. The inspection of a hexagonal pipe to avoid its failure and thus to ensure safe operation of a drilling machine is becoming increasingly urgent and important. In this study, the excitation and propagation of ultrasonic guided waves for the purpose of detecting defects in hexagonal pipes are proposed. Dispersion curves of hexagonal pipes are firstly derived by using semianalytical ﬁnite element method. Based on these dispersion curves, longitudinal L (0, 2) mode at 100 kHz is selected to inspect hexagonal pipes. A ring of piezoelectric transducers (PZTs) with the size of 25 mm × 5 mm ×0.5 mm is able to maximize the amplitude of L (0, 2) mode and successfully suppress the undesired L (0, 1) mode in the experiments. Numerical and experimental studies have shown that the displacement field of L (0, 2) mode at 100 kHz is almost uniformly distributed along the circumferential direction. Furthermore, L (0, 2) mode ultrasonic guided waves at 100 kHz are capable of detecting circular through-hole damages located in the plane and near the edge in a hexagonal pipe. Our study results have demonstrated that the use of longitudinal L (0, 2) mode ultrasonic guided wave provides a promising and effective alternative for the detection of defects in hexagonal pipe structures.